Synthesis and Characterization of Gallium Oxide Nanoparticles using Pulsed Laser Deposition - Hameed, Mohammed M.; Al-Samarai, Abdul-Majeed E.; Aadim, Kadhim A. (Iraqi Journal of Science, 2020)
In this paper, the productions of gallium oxide (Ga2O3) nanoparticles were achieved via using the Nd: YAG laser deposition method with a fundamental wavelength (1064 nm). These nanoparticles were characterized by using different methods such as X-ray diffractometer (XRD), atomic force microscopy (AFM) and Ultraviolet–visible (UV–vis) spectroscopy. To examine the effects of laser energy on the properties of nanoparticles, the experimental results and theoretical considerations were prepared by the effective method of pulse laser deposition. The synthesis of Ga2O3NPs) was achieved with different ranges of energies (500 to 900 mJ). Average crystallite sizes of the synthesized nanoparticles were found to be in the range of 15-37 nm. On the other hand, the AFM images showed that the size is ranging between 60 and 85 nm. Optical parameters of the samples showed a strong dependence on average crystallite size.